Effect of Over-Pressure on Pipeline Structural Integrity - Igor Martić; Aleksandar Sedmak; Nenad Mitrović; Simon Sedmak; Ivana Vučetić (Tehnički Vjesnik, 2019)
The effect of proof over-pressure on pipeline structural integrity using fracture mechanics parameters is analysed in the case of pipeline in Reversed Hydro Power Plant, made of High Strength Low Alloyed steel with 800 MPa tensile strength due to special design requirements. To assess its structural integrity, extensive testing of the full-scale prototype had been performed, including hydrostatic pressurizing. Since plastic strain was recorded during proof over-pressurizing, special attention is given to the fact that this is actually a mechanism for crack initiation and propagation. To investigate this effect micromechanical modelling is considered, as well as the Failure Assessment Diagramme. It is shown that over-pressuring has potential detrimental effect on pipeline safety, i.e. structural integrity.